Optimizing Soybean Chlorophyll Content Under Drought Stress: Unveiling the Potential of Biostimulants from Padina minor Yamada with Different Solvent Extraction - De Yudanur, Parissa Anandita; Noli, Zozy Aneloi; Mansyurdin, Mansyurdin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Biostimulants are natural compounds that can stimulate plant growth. Biostimulants from Padina minor contain secondary metabolites and growth-regulating substances needed in various plant growth metabolisms, including soybeans (Glycine max L.). Biostimulants also play a role in enhancing drought stress tolerance in plants. Several solvents are used to extract natural compounds found in P. minor. This study aims to investigate the effect of P. minor biostimulant extracted using various solvents on soybeans' chlorophyll content under different drought stress levels. The study used a completely randomized design (CRD) with two factors: a. Solvent (control, aquadest, methanol, and ethanol) and b. Soil field capacity (100%, 75%, 50%, and 25%). Applying P.minor as biostimulant extracted with methanol solvent showed higher average chlorophyll a, b, and total chlorophyll than other solvent types. Imposing stress up to 25% did not significantly affect soybean chlorophyll levels. However, the interaction between soil field capacity and P. minor extract from methanol solvent can trigger resilience response to drought conditions up to 25% soil field capacity and provide the highest average chlorophyll content compared to other treatments during the soybean vegetative period. Methanol is the best solvent for extracting P. minor as biostimulant and can provide the highest average chlorophyll content at 25% soil field capacity.